Pengembangan Penalaran Ilmiah Mahasiswa dalam Mata Kuliah Filsafat Ilmu melalui Pendekatan Ekstrapolasi - Maman Rachman (Universitas Negeri Malang, 2016)
This action research is an effort to enhance the students' scientific reasoning in the philosophy of science through extrapolation approach. This study was conducted in two cycles within 6 months. The data were collected through observation, interview, and documentation, and were analyzed descriptively. The results indicated that extrapolation approach could enhance the students' scientific reasoning by proposing basic and advance questions; submitting actual, controversial, and broad problems; and giving "recipe" and problematic tasks